New Plastic for Toys is Five Times Tougher! - Dow Chemical Company (1943)
Color print advertisement for Styron, the trade name for Styrenic plastics historically manufactured and sold by the Dow Chemical Company for a variety of consumer applications. The advertisement features a photograph of a young boy on a black background, surrounded by toys made from Styron. The accompanying text describes the durability of Styron 475.
Keywords: Dow Chemical Company; Advertising; Chemical industry; Corporations; Plastics; Plastics industry and trade; Plastic toys; Children in advertising; Advertising, Industrial